2013
DOI: 10.1186/2046-4053-2-44
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of monotherapies and combination therapies for patients with hypertension: protocol for a systematic review with network meta-analyses

Abstract: BackgroundHypertension has been cited as the most common attributable risk factor for death worldwide, and in Canada more than one of every five adults had this diagnosis in 2007. In addition to different lifestyle modifications, such as diet and exercise, there exist many pharmaco-therapies from different drug classes which can be used to lower blood pressure, thereby reducing the risk of serious clinical outcomes. In moderate and severe cases, more than one agent may be used. The optimal mono- and combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…According to the National Health and Nutrition Examination Survey (NHANES) report in 2011e2012, the burden of HTN was estimated to be 29.1% among the American adult population [2]. Previous studies have shown that outcomes of HTN can be reduced by lowering blood pressure levels [3,4]. A meta-analysis revealed that a 10-mmHg decrease in systolic blood pressure (SBP) and a 5-mmHg decrease in diastolic blood pressure (DBP) reduced the risks of coronary heart disease (CHD) and stroke by 20% and 32%, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Health and Nutrition Examination Survey (NHANES) report in 2011e2012, the burden of HTN was estimated to be 29.1% among the American adult population [2]. Previous studies have shown that outcomes of HTN can be reduced by lowering blood pressure levels [3,4]. A meta-analysis revealed that a 10-mmHg decrease in systolic blood pressure (SBP) and a 5-mmHg decrease in diastolic blood pressure (DBP) reduced the risks of coronary heart disease (CHD) and stroke by 20% and 32%, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PubMed/MEDLINE will be searched to identify other additional observational studies using a compiled list of the unique PubMed/MEDLINE identification numbers of all relevant articles, and a related article search will be performed. This technique has been shown to be effective in identifying relevant studies, increases efficiency in study identification in the presence of an already large evidence base [48] and is being used as part of complex evidence syntheses [4951]. We will also contact authors of primary publications and/or collaborators to check if they are aware of any studies we may have missed.…”
Section: Methodsmentioning
confidence: 99%
“…There are various treatments available for ADHD, including pharmacotherapy, behavioral therapy, cognitive behavioral therapy, parent-based interventions, Nutritional Therapy (NT), Cognitive Rehabilitation Training (CRT), group therapy and self-esteem enhancement [8]. C-CRT and NT are modern treatments with relatively acceptable empirical support [11,12].…”
Section: Introductionmentioning
confidence: 99%